Pengaruh model picture and picture berbasis pendekatan saintifik terhadap hasil belajar kognitif IPAS kelas V SDN Se-Gugus Anggrek Ngrampal - Arya Esta Pratama; Fadhil Purnama Adi (Universitas Sebelas Maret, 2026)
This study aims to determine whether there is an effect of using the picture and picture model based on the scientific approach on the cognitive learning outcomes of IPAS in grade V SDN in Anggrek Ngrampal group. This research used experimental method with pretest-posttest control group design. The subjects of this study were fifth grade students at SDN Bener 2 and SDN Bener 4, totaling 29 students. Data were collected through tests and observations. The data analysis technique used mann-whitney test by comparing the results of pretest and post-test in control class and experimental class. The results showed that the use of a picture and picture learning model based on a scientific approach was able to improve the cognitive learning outcomes of IPAS class V material on my rich biodiversity. With the results of the value with the mann-whitney test, the significance value is <.001 this result is less than the significance level of 0.05. This study concluded that the picture and picture learning model based on a scientific approach in improving the ability of IPAS cognitive learning outcomes in grade V students of SDN Se-gugus Anggrek.